Comparison of Features of Corona Virus in Confirmed and Unconfirmed Patients In Lahore - Muhammad Imran Hasan Khan , Muhammad Maqsood , Muzammal Aslam Kataria , Asif Sagheer , Abdul Basit , Zohaib Abbas Khan (Journal of Rawalpindi Medical College, 2020)
Introduction: Coronavirus has spread rapidly in Pakistan. These patients were kept at quarantine facilities on suspicion, even before RT-PCR was done. We were able to collect clinical, laboratory, and management features from them. Objective: To assess the features of Corona confirmed and unconfirmed patients, and compare them. It could help in deciding if confirmed and unconfirmed patients were correctly identified and managed appropriately. Material and Methods: Retrospective, Descriptive, Crossectional study between 8th April to 30th April 2020. Patient data was collected from different sites retrospectively, on a Performa. Clinical, Laboratory, and Management data as collected. It was analyzed on SPSS 23. All patients in quarantines and ICU were included, irrespective of their corona PCR status, if the treating physicians had a strong suspicion. Home quarantine and less than 15-year old patients were excluded. Results: Clinical features showed more preponderance for males and smokers. Chronic disease patients were also significantly involved. Fatigue, nasal congestion, runny nose, sickness, and vomiting were more common in confirmed patients. CURB 65 scores 3 and 4 were more in unconfirmed patients. CT involvement was more common in unconfirmed patients as was high white cells and neutrophils. More patients had mechanical ventilation in the unconfirmed group, and they also had more secondary infections and shock. Antibiotic use was more common in the confirmed group. Conclusion: Corona was more common in males and smokers. Though fever and cough were common, the presence of fatigue, runny nose, nasal congestion sickness, and vomiting discriminated confirmed patients. Antibiotics should be used irrespective of RT-PCR results, especially if CT showed an abnormality.